Microstructural and Mechanical Characterization of Square‐Celled TRIP Steel Honeycomb Structures Produced by Electron Beam Melting. Issue 7 (13th April 2020) - Burkhardt, Christina; Wagner, Ruben; Baumgart, Christine; Günther, Johannes; Krüger, Lutz; Biermann, Horst
Abstract : The powder‐bed additive manufacturing (AM) technology electron beam melting (EBM) is suitable for the production of metallic components with complex geometries. Therefore, it is an appropriate method of generating lightweight structures to save material and energy, which is of high importance for the transport industry. The microstructure of additive manufactured materials is usually characterized by columnar grains shape, oriented along the building direction. Therefore, the mechanical properties are strongly affected by anisotropy. Herein, the synthesis and the microstructure of CrMnNi transformation‐induced plasticity (TRIP) steel by EBM is examined. This steel is well suited for AM due to the formation of fine‐grained microstructure instead of columnar one through multiple‐phase transformations. Square‐celled honeycomb structures are produced and improved to generate damage‐tolerant struts. The removal of slightly sintered powder from the cavities of square‐celled structures is quantified. Out‐of‐plane compression tests at quasistatic loading rates show that the strength of honeycomb structures rises with increasing energy input during EBM due to lower material porosity. Therefore, an enhanced mechanical energy absorption capacity is achieved which is favorable for the production of cellular structures. Abstract : Powder‐bed additive manufacturing technology electron beam melting (EBM) is applied on metastable austenitic transformation‐induced plasticity (TRIP) steel powder producing square‐celled honeycomb structures. The microstructure of cell walls consists of fine‐grained microstructure revealed by electron backscattered diffraction (EBSD). An increase in the beam energy input of EBM results in thicker struts manufacturing, higher global density, and higher strength of honeycomb structures.